A Study on the Impact of Exchange Rate Changes on Trade Balances: An Analysis of China Case and Some Recommendations to Vietnam - Quang Linh, Nguyen; Thi Tai Linh, Nguyen (VNU Journal of Science: Policy and Management Studies, 2026)
Abstract: This paper studies the impact of exchange rate fluctuations of the Chinese Yuan (CNY) against the local currencies of China's 20 major trading partners on China’s bilateral trade balance from 2013 to 2024, aiming to identify the transmission mechanism between exchange rates and trade balances. The study applies panel data regression methods to analyze both the direct and indirect effects of exchange rate fluctuations on China’s trade balance with these partners, including the estimation of exchange rate coefficients using POLS, REM, FEM, and FGLS regressions, and the assessment of the probability of trade imbalance occurrences, with the exchange rate as a significant predictive factor, using Logit regression. Based on the empirical findings, the paper proposes policy implications for Vietnam, particularly in formulating flexible exchange rate management policies to mitigate the negative effects of China’s monetary policy. Keywords: Exchange rate changes, trade balance, impact.